Dyke Davidoff Masson Syndrome with Abdominal Epilepsy-Rare Presentation - Srivastava, Shitanshu; Singh, Rajat Pratap; Srivastava, KL (Asian Journal of Medical Sciences, 2013)
Dyke Davidoff Masson Syndrome (DDMS) with abdominal epilepsy, is a rare clinical condition. It is characterized by severe abdominal pain with seizures, facial asymmetry, contralateral hemiparesis, and mental retardation. Diagnosis is made clinically coupled with radiological features which include cerebral hemiatrophy with homolateral hypertrophy of the skull and sinuses along with abnormal EEG and response to antiepileptic drugs. Here we report a case of DDMS with abdominal epilepsy in a 10 year old male child who presented with recurrent episodes of severe abdominal pain followed by seizures, hemiparesis and mental retardation. CT and MRI showed hemiatrophy of right cerebral hemisphere. DOI: http://dx.doi.org/10.3126/ajms.v3i2.6172 Asian Journal of Medical Sciences 3(2012) 25-28